2022
DOI: 10.3389/fcvm.2022.791875
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Sequencing of Immune Cells in Human Aortic Dissection Tissue Provides Insights Into Immune Cell Heterogeneity

Abstract: BackgroundInflammation plays an important role in the progression of sporadic aortic dissection (AD). Immune cells, especially macrophages, infiltrate the aorta and secrete inflammatory cytokines and matrix metalloproteinases to cause degradation of the extracellular matrix, thereby contributing to the pathogenesis of AD. However, the cellular heterogeneity within these immune cells has not been fully characterized.MethodsWe used single-cell RNA sequencing to profile the transcriptomes of all immune cells in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Inflammation is an important factor leading to the occurrence and progression of AD [16][17][18]. A variety of immune cells can participate in the occurrence of AAD by switching to a proinflammatory phenotype and releasing inflammatory factors [18][19][20]. A previous study found that DDR-related proteins were involved in inflammatory responses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is an important factor leading to the occurrence and progression of AD [16][17][18]. A variety of immune cells can participate in the occurrence of AAD by switching to a proinflammatory phenotype and releasing inflammatory factors [18][19][20]. A previous study found that DDR-related proteins were involved in inflammatory responses [7].…”
Section: Introductionmentioning
confidence: 99%
“…More evidence came from gene expression analysis in which inflammatory factor genes, for example, S100A9, C1QA, and TIMP1, showed higher expression in visceral adipose tissue (VAT) than in subcutaneous adipose tissue (SAT) (Figure 5E; Figure S15F, Supporting Information). [45][46][47] On the other hand, it is known that subcutaneous fat is more involved in energy metabolism than visceral fat. We found that energy-related metabolism GO terms (i.e., mitochondrion organization and positive regulation of angiogenesis) were significantly enriched with genes in the positive SHAP regions for M2 cells in the ULB (Figure S15B, Supporting Information).…”
Section: Decooc Deconvoluted the Chromatin Architecture In M2 Cells R...mentioning
confidence: 99%
“…development of aortic dissection (108). As for mesenchymal stem cells (MSC), because of their anti-inflammatory and repairing effects, whether they can be used in the treatment of AAD needs to be explored in more depth in the future.…”
Section: Transcriptomics and The Discovery Of Aad Biomarkersmentioning
confidence: 99%
“…Activation of Janus kinase 2 (JAK2) ( 104 , 105 ) and elevated plasma ANGPT2 levels ( 106 , 107 ) are suggestive of upregulation of pro-inflammatory cytokines in AAD. In turn, these upregulated proinflammatory cytokines lead to activation of chemotactic and other immune cells, especially neutrophils and T cells, which can further secrete inflammatory factors and granzyme, exacerbating the medial lesion and leading to the development of aortic dissection ( 108 ). As for mesenchymal stem cells (MSC), because of their anti-inflammatory and repairing effects, whether they can be used in the treatment of AAD needs to be explored in more depth in the future.…”
Section: Discovery Of Aad Biomarkers Based On Multi-omics Technologiesmentioning
confidence: 99%
See 1 more Smart Citation